2021
DOI: 10.3390/antiox10111750
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Telomere Homeostasis with Oxidative Stress and Cardiac Dysfunction in Human Ischaemic Hearts

Abstract: Although the roles of telomeres and oxidative stress in ischaemic cardiomyopathy (ICM) are known, mechanisms of telomere homeostasis and their relationship with oxidative stress are incompletely understood. We performed two RNA-seq analyses (mRNA n = 23; ncRNA n = 30) and protein validation on left ventricles of explanted hearts from ICM and control subjects. We observed dysregulation of the shelterin and cohesin complexes, which was related to an increase in the response to cellular oxidative stress. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…RNA extraction, determination of purity and integrity of RNA samples, mRNA-seq, and ncRNA-seq analysis were performed as previously described by Tarazón et al [ 14 ] and are extensively described in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction, determination of purity and integrity of RNA samples, mRNA-seq, and ncRNA-seq analysis were performed as previously described by Tarazón et al [ 14 ] and are extensively described in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…It constitutes a significant economic and public health burden with high morbidity and mortality rates worldwide [1], mainly due to ischemic heart diseases, and is a leading global cause of death [2]. The pathological process of the heart is associated with an altered expression profile of molecules that are important for cardiac function [3][4][5][6]; however, the molecular mechanisms of gene regulation remain incompletely understood. Most human protein-coding genes are likely under microRNA control through microRNA-binding sites located in their untranslated and amino acid coding regions [7,8] and, therefore, microRNA are probably involved in nearly all developmental and pathological processes.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of myocardial damage in ischaemic heart disease, Tarazón et al [ 7 ] explore telomere homeostasis and its relationship with oxidative stress as a novel potential mechanism and biomarker. Through RNA-seq studies of left ventricular samples of explanted hearts from ischaemic cardiomyopathy patients and control subjects, the authors observed a dysregulation of the shelterin and cohesin complexes, associated with an increase in the response to cellular oxidative stress.…”
mentioning
confidence: 99%